Study on the Socioeconomic Conditions Affecting the Income of Culinary Vendors at the Tapal Kuda Tourist Attraction in Ambon City - Hamuli, Nur Winda; Sihasale, Daniel Anthoni; Tetelepta, Edward Gland (Jurnal Pendidikan Geografi Unpatti, 2022)
Optimally developing tourism can increase economic growth, create jobs, and increase regional income. This study aimed to determine how Liang Beach tourism was managed during the COVID-19 pandemic in Liang Village District. Salahutu, Regency. Central Moluccas. This research was conducted in Liang Village, Salahutu District, Central Maluku Regency, October 3–November 3, 2022. The population in this study was 100 people. The study sample was 100 randomized people. The variables used were facility management, central facilities, supporting facilities, and supporting facilities. Data analysis techniques used the Miles and Huberman models: data reduction, data display, and conclusion drawing and verification. The study results show that managing Liang Beach's tourism objectives during the COVID-19 pandemic will involve improving existing infrastructure, such as cleaning tourist attraction areas and working on road infrastructure. Managers will work closely with the Ambon City Regency Tourism Office.